2015
DOI: 10.4024/08cu15a.jbpc.15.03
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate nontoxicity: the genesis of a scientific fact

Abstract: Repetition of a 1978 experiment on the toxicity of glyphosate chemicals in water-flea Daphnia magna showed surprising results. In the 31 years which had passed between the two series of experiments, the toxicity of glyphosate had apparently become 300 times stronger! Further investigation into this enigmatic paradox discloses unfortunate aspects of laboratory researcher cultures as well as fundamental challenges in current regulatory approval of chemicals and the epistemology of risk-assessment. Keywords: flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…And, in long-term studies we found that low concentrations (0.05-0.45 ppm) of either glyphosate (glyphosate IPA) or GBH Roundup formulation (contains glyphosate IPA as active ingredient) had adverse effects on growth and reproduction (Cuhra et al, 2013). Several problematic issues relating to existing assumptions on ecotoxicity of glyphosate were identified, amongst these the fact that glyphosates are a family of chemicals with distinctly differing physical properties and biological effects, notably levels of contaminants from different manufacturing processes, and basic properties such as solubility in water (Cuhra, 2015c). Also, numerous studies on toxicity and ecotoxicity of glyphosate and glyphosate-based herbicides were performed by commercial laboratories at a time when such research did not adhere to later quality requirements.…”
Section: Review Of Recent Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…And, in long-term studies we found that low concentrations (0.05-0.45 ppm) of either glyphosate (glyphosate IPA) or GBH Roundup formulation (contains glyphosate IPA as active ingredient) had adverse effects on growth and reproduction (Cuhra et al, 2013). Several problematic issues relating to existing assumptions on ecotoxicity of glyphosate were identified, amongst these the fact that glyphosates are a family of chemicals with distinctly differing physical properties and biological effects, notably levels of contaminants from different manufacturing processes, and basic properties such as solubility in water (Cuhra, 2015c). Also, numerous studies on toxicity and ecotoxicity of glyphosate and glyphosate-based herbicides were performed by commercial laboratories at a time when such research did not adhere to later quality requirements.…”
Section: Review Of Recent Findingsmentioning
confidence: 99%
“…Roundup and similar formulated glyphosate herbicides contain various adjuvants and inert ingredients. We have described some of the confusion that enshrouds ecotoxicological and toxicological assessments of these compounds, which are seen as significantly contributing to toxicological properties of formulated herbicides (Cuhra et al, 2013;Cuhra, 2015c). Recognizing the inherent complexity of assessing compounds which are protected commercial products and which have properties known to producers, but partly unavailable to scientists and regulators, we suggest that all ingredients in herbicide formulations should be regulated and subject to mandatory declaration.…”
Section: Toxicity and Ecotoxicity Of Glyphosates And Gbhsmentioning
confidence: 99%
See 3 more Smart Citations